SOME NOTES ABOUT THE NATURE RESERVE PULAU PANAITAN (PRINSENEILAND) IN STRAIT SUNDA, with special reference to the avifauna - A. HOOGERWERF (TREUBIA, 1953)
Fro!ll August the 30th till October the 5th 1951, Kebun Raya Indonesia(Botanical Gardens) at Bogor organized an expedition to the islandmentioned above.Up till then the island was nearly "terra incognita" from a scientific point of view, for no botanical or zoological investigation had ever beenmade, though some scientists (a.o. MOLLIER, DAMMERMAN, ENDERT) paid short visits to the area.